The Effect of Good Corporate Governance, Sustainability Reporting, and Profitability on Firm Value in the Energy Sector Listed on the Indonesia Stock Exchange for the 2020–2024 Period - Neni Sarbinny; Iwan Setiadi (SEAN Institute, 2026)
This study aims to analyze the effect of Good Corporate Governance, Sustainability Reporting, and Profitability on Firm Value in energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Good Corporate Governance is proxied by Independent Commissioners, Audit Committee, and Institutional Ownership, while Profitability is proxied by Return on Assets (ROA), and Firm Value is measured using Price to Book Value (PBV). This study employs a quantitative approach using secondary data in the form of annual reports and sustainability reports. The analytical method used is panel data regression with the assistance of EViews software. The results show that partially, Independent Commissioners have a significant effect on Firm Value, whereas the Audit Committee, Institutional Ownership, Profitability (ROA), and Sustainability Reporting do not have a significant effect on Firm Value. Simultaneous testing results indicate that Good Corporate Governance, Sustainability Reporting, and Profitability collectively have a significant effect on Firm Value. The coefficient of determination (R-Square) is 0.657480, indicating that the research model explains 65.75% of the variation in Firm Value, while the remaining 34.25% is influenced by other factors outside the model. These findings indicate that in energy sector companies, corporate governance mechanisms particularly the role of independent commissioners are the most important factors considered by investors in assessing firm value. Meanwhile, profitability and sustainability reporting aspects have not been fully responded to by the market as determinants of firm value in the short term.